Effectiveness of Internal Audit in Supporting Internal Control and Prevention of Fraud - Sudirman, Sudirman; Sasmita, Halida; Djabir D, Muhammad; Krisnanto, Budhi; Muchsidin, Feronica Fungky (STIEM BONGAYA, 2021)
This study aims to analyze the effectiveness of internal audit at PT Bank Sulselbar Makassar in supporting internal control over fraud. This study uses a qualitative approach with the method of documentation, interviews and questionnaires to the internal auditors, anti-fraud department, and management as data collection methods. After the data was collected, data analysis was carried out using descriptive methods and measuring effectiveness. Based on the study results, it can be stated that the role of the Internal Audit Group as an internal audit in improving the internal control system for fraud at Bank Sulselbar has been influential. The internal audit of Bank Sulselbar has the authority to monitor the follow-up to the results of the audit conducted by the auditor. Monitoring activities are carried out to ensure that corrective actions have been carried out adequately and effectively. Thus, the company will implement better internal controls in the future because assessments and corrective actions for weaknesses and errors found are always carried out. There are three elements to prevent and detect fraud, namely a culture of honesty (personal), management responsibility to evaluate fraud risk (through internal control), and supervision by the audit committee (internal audit).